Localised task-dependent motor-unit recruitment in the masseter - Schindler, Hans J.; Hellmann, Daniel; Giannakopoulos, Nikolaos Nikitas (Journal of oral rehabilitation, 2014)
Localised motor-unit (MU) recruitment in the masseter was analysed in this study. We investigated whether differential activation behaviour, which has already been reported for distant masseter regions, can also be detected in small muscle subvolumes at the level of single MUs. Two bipolar fine-wire electrodes and an intra-oral 3D bite-force transmitter were used to record intra-muscular electromyograms (EMG) resulting from controlled bite-forces of 10 healthy human subjects (mean age 24·1 ± 1·2 years). Two-hundred and seventeen decomposed MUs were organised into localised MU task groups with different (P < 0·001) force-direction-specific behaviour. Proportions of MUs involved in one, two, three or four examined tasks were 46%, 31%, 18% and 5%, respectively. This study provides evidence of the ability of the neuromuscular system to modify the mechanical output of small masseter subvolumes by differential control of adjacent MUs belonging to distinct task groups. Localised differential activation behaviour of the masseter may be the crucial factor enabling highly flexible and efficient adjustment of the muscle activity in response to complex local biomechanical needs, for example, continually varying bite-forces during the demanding masticatory process.